Calitatea vieţii persoanelor diagosticate cu boli rare în România - Olah, Şerban; Popoviciu, Ioan; Popoviciu, Salomea; Bîrle, Delia (Calitatea Vieții, 2012)
This research had as a main objective the exploration of the quality of life of people diagnosed with rare diseases in Romania. The research method used a sociological survey, and the instrument used was a 42 item survey specifically designed for this study. The survey was administered to a number of 645 subjects selected through snowball sampling. The results of the study show that the situation of Romanian patients that suffer from a rare disease is subjectively perceived by them as: (1) quite difficult, if we refer to finantial situation or the support received from the Romanian state; (2) moderate in regard to the satisfaction with medical services, NGOs, living conditions or the emotional and psychological health; and (3) generally good, if we analyze the support given by family or the perceived relationship with the Church or God.